2020
DOI: 10.3390/resources9080096
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Circular Economy in Ukraine: The Context of European Integration

Abstract: The current model of resource management mainly contributes to mass short-term consumption, which creates an unstable and extremely critical situation on the planet. Going beyond the traditional industrial model of Take-Make-Waste, the circular economy aims to reduce waste (and therefore minimize costs) and to redefine sustainable development. This entails a gradual separation of economic activity from the consumption of scarce resources and the removal of waste from the system. In order to foreground the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Because improving governance is the key to promoting and ensuring sustainable economic growth for countries at all stages of development, the econometric analysis supports a series of policies/guidelines that could be considered by the policy makers and public institution leaders within the EU, namely: (i) bolster commitment in conducting public affairs, responsibility in managing public resources, and sound measures targeted to maintain the balance between spending revenues and saving funds for the future; (ii) amplified coordination and credibility/transparency of the actions that support financial stability, along with citizen's positive perceptions of public authorities because this endeavor has shown that agents' and citizens' participation and perceptions are beneficial to strengthening good public governance; (iii) on previous lines, enhancing the role of stakeholders at local, regional, national, and international levels and allowing them to effectively contribute to the decision-making process; (iv) further, leveraged cooperation between all actors involved in designing and implementing the public policies and providing public services to citizens, particularly in the case of environmental protection, which is one of the uppermost credentials in supporting sustainable economic development [42,43]; (v) enhanced accountability in the public sector because the estimations have proved that there is a strong positive bidirectional link between public spending and the voice and accountability dimension of good public governance, with further positive spillovers into economic welfare (increases in GDP per capita and decreases in the poverty risk).…”
Section: Discussionmentioning
confidence: 99%
“…Because improving governance is the key to promoting and ensuring sustainable economic growth for countries at all stages of development, the econometric analysis supports a series of policies/guidelines that could be considered by the policy makers and public institution leaders within the EU, namely: (i) bolster commitment in conducting public affairs, responsibility in managing public resources, and sound measures targeted to maintain the balance between spending revenues and saving funds for the future; (ii) amplified coordination and credibility/transparency of the actions that support financial stability, along with citizen's positive perceptions of public authorities because this endeavor has shown that agents' and citizens' participation and perceptions are beneficial to strengthening good public governance; (iii) on previous lines, enhancing the role of stakeholders at local, regional, national, and international levels and allowing them to effectively contribute to the decision-making process; (iv) further, leveraged cooperation between all actors involved in designing and implementing the public policies and providing public services to citizens, particularly in the case of environmental protection, which is one of the uppermost credentials in supporting sustainable economic development [42,43]; (v) enhanced accountability in the public sector because the estimations have proved that there is a strong positive bidirectional link between public spending and the voice and accountability dimension of good public governance, with further positive spillovers into economic welfare (increases in GDP per capita and decreases in the poverty risk).…”
Section: Discussionmentioning
confidence: 99%
“…The BRICS nations (Brazil, Russia, India, China, South Africa), like China and India, came forward in support of green growth and reducing carbon investments after this was implemented by North America and Europe. Likewise, firms and businesses are becoming more concerned about their actions or practices and their consequences, and are increasing their investments in environmental protection issues, hence becoming more environmentally oriented [2], which also means that the circular economy has gained importance [7]. The main drivers of environmental concern and green innovations are external pressure, such as strong government regulations, the desire to improve reputations by achieving competitive advantage, and the need to increase production performance with accompanying cost reductions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in numerous scientific works, increased attention is paid to the development of the tourism industry, due to its important contribution to the economy of each country. This is confirmed by a number of studies on the problems of tourism in the circular economy (Shpak et al 2020;Meijerink and Keegan 2019;Sutherland and Jarrahi 2018;Voltes-Dorta et al 2014). It is analyzed how tourism can support the development of the circular economy, applying a theory that emphasizes changes in what tourists do, rather than in tourism products and services (Flemming and Baerenholdt 2020).…”
Section: Types Of Tourismmentioning
confidence: 87%